PENINGKATAN KOMPETENSI DIGITAL KREATIF MELALUI VIDEO MARKETING BERBASIS 7 KEBIASAAN HEBAT ANAK INDONESIA PADA MAHASISWA - Isriyah, Mudafiatun; Kustiyowati, Kustiyowati; Rahmawati, Weni Kurnia (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2025)
In facing the challenges of the digital economy and the global recession, the ability to produce creative digital-based content is an important need for students and young Micro, Small, and Medium Enterprises (MSMEs). The community service partners in this activity consist of a community of student entrepreneurs and young Micro, Small, and Medium Enterprises (MSMEs) in Jember City, who have products but have difficulty in promoting and building brand visibility through digital media. The main problems faced by partners are low skills in creating effective video marketing content and the suboptimal instillation of character values ​​in business promotion. As a solution, the community service team carried out intensive training and mentoring based on the 7 Great Habits of Indonesian Children combined with basic video marketing techniques. The methods used include technical video-making workshops, character-based product storytelling sessions, and direct practice in creating and publishing promotional videos on social media. The results of the activity showed a significant increase in participants' skills in creating short videos that are interesting and contain character values, as well as increased participant confidence in marketing products digitally. This activity shows that a value-based training approach and creative practice can be an effective strategy in increasing the digital capacity of the younger generation and MSMEs in facing today's economic challenges.